Socio-Developmental Network Analysis: Establishing a Research Method to Examine Socio-Contextual Dynamics of Children in the Mockingbird FamilyTM - Emi Patmisari; Helen McLaren; Michelle Jones (Social Sciences, 2023)
In recent years, social network analysis has had its own distinctive theoretical and methodological underpinnings. This article proposes a novel method for the application of a fused mixed-methods approach and social network analyses that incorporates the critical aspects of numerous characteristics of children’s social development in a statutory care setting. We collected data from children involved in the Mockingbird Family out-of-home care model, following its implementation in Australia. Our approach involves three steps: social-developmental network indicators, relational dynamics, and social-developmental network narrative. We contend that this approach has the potential to provide powerful data representation that facilitates the understanding of the complexities of children’s social development, the links between different positions and roles of children, and their social network in the Mockingbird family. Using exemplars, we show the potential of the research method to unearth rich data for seeking to understand the system change important for strengthening children’s safe and protective environments.